Exploring the environmental fate of novel brominated flame retardants in a sediment-water-mudsnail system: Enrichment, removal, metabolism and structural damage. (October 2020) - Wang, Yawen; Ling, Siyuan; Lu, Cong; Jiang, Lingling; Zhou, Shanqi; Fu, Mengru; Zhang, Wei; Lin, Kuangfei; Zhou, Bingsheng
Abstract: Novel brominated flame retardants (NBFRs) are now ubiquitous in the environment with the extensive production and application. In the present study, pentabromotoluene (PBT), hexabromobenzene (HBB) and decabromodiphenyl ethane (DBDPE) were spiked into the sediments where mudsnails ( Bellamya aeruginosa ) were cultivated. In the 35-day enrichment process, the highest concentration of the three NBFRs measured in mudsnail is 2.0 mg/kg, 22 mg/kg and 5.2 mg/kg dry weight (dw), respectively. The average enrichment of NBFRs in viscera was about 3 times of pleopod with the same mass. Meanwhile, the parent mudsnails can transfer NBFRs to their offspring. The removal half-life of the three NBFRs was in the range of 2.6 and 5.7 days according to the first-order kinetic equation. Several degradation products of the NBFRs were detected in mudsnail samples, which were exposed to single substance. 2, 4, 6-tribromotoluene was identified as degradation product of PBT; 1, 2, 4, 5-tetrabromobenzene and 1, 2, 4-tribromobenzene were identified as debromination products of HBB. Possible degradation pathways were further proposed. Additionally, mudsnails after exposed to 50 mg/kg of NBFRs were observed under a scanning electron microscope, indicating that shrinkage, tissue hyperplasia and perforation occurred on the visceral surface. Such damage might be related to the accumulation of more pollutants in mudsnails viscera. As one of the few studies to explore the biological process of NBFRs, our observation could provide a scientific basis for evaluating the environmental risks of NBFRs to benthic organisms. Graphical abstract: Image 1 Highlights: A sediment-water-mudsnail system was established to explore the environmental fate of NBFRs. The bioaccumulation potential of mudsnail viscera was greater than that of pleopod. Biodegradation of the selected three NBFRs was a process of stepwise debromination. Damages in microscopic surface morphology of mudsnail viscera were clearly observed by SEM. Abstract : This study demonstrates the environmental fate of the three NBFRs in a sediment-water-mudsnail system for the first time.